Pragmatisme Multilateral dalam Momen Keketuaan Indonesia di G20 dan ASEAN, 2022-2023 - Rosyidin, Mohamad (Jurnal Politica, 2023)
Most international relations literature conceives a positive viewpoint on multilateralism. Multilateral diplomacy is often associated with collective efforts to solve various problems at the regional or global level. Indonesia has long practiced multilateral diplomacy as part of its commitment to create a better world as mandated by the constitution. However, under the leadership of President Joko Widodo (Jokowi), Indonesia’s multilateral diplomacy puts a strong emphasis on achieving national rather than collective interests. Using a case study of Indonesia’s G20 and ASEAN presidency, this article argues that Indonesia’s multilateral diplomacy was dominated by the principle of pragmatism which is oriented towards the pursuit of short-term interests, especially the economy, rather than strategic efforts to solve international problems. This principle of multilateral pragmatism undermines Indonesia’s reputation as a middle power which is expected to contribute to solving global problems.AbstrakKebanyakan literatur hubungan internasional memandang secara positif tentang multilateralisme. Diplomasi multilateral sering kali diasosiasikan dengan upaya kolektif untuk memecahkan aneka persoalan di tingkat regional atau global. Indonesia sejak lama mempraktikkan diplomasi multilateral sebagai bagian dari komitmen menciptakan dunia yang lebih baik sebagaimana amanat konstitusi. Namun, di bawah kepemimpinan Presiden Joko Widodo (Jokowi), diplomasi multilateral Indonesia menekankan pada pencapaian kepentingan nasional ketimbang kepentingan kolektif. Menggunakan studi kasus presidensi Indonesia di G20 dan ASEAN, artikel ini mengemukakan argumen bahwa diplomasi multilateral Indonesia di kedua forum tersebut didominasi prinsip pragmatisme yang berorientasi pada pengejaran kepentingan jangka pendek terutama ekonomi alih-alih upaya strategis memecahkan persoalan internasional. Prinsip pragmatisme multilateral ini dapat melemahkan reputasi Indonesia sebagai kekuatan menengah yang diharapkan dapat berkontribusi bagi pemecahan masalah-masalah global.